TECHNOLOGY READINESS INDEX DALAM PENGADOPSIAN SISTEM PEMBAYARAN QRISS - Ni Putu Yeni Astiti; I Made Surya Prayoga; I Gusti Ayu Imbayani (Fakultas Ekonomi Universitas Warmadewa, 2023)
This research was conducted at SMEs in Denpasar City by distributing questionnaires. The object of this research is SMEs actors in Denpasar City. Measuring the readiness of SMEs actors to adopt the Quik Response Code Indonesia Standard (QRIS) payment system uses the technology readiness index (TRI), which consists of four dimensions, namely: optimism, innovativeness, discomfort, and insecurity. The sample used in this study consisted of 98 SME actors in Denpasar City. The sample was determined by a simple random sampling techniqu e.This study found that the average score for the dimensions of optimism and discomfort was in the very high score category, while the other two dimensions, namely innovativeness, and insecurity were included in the high score category.